Effect of temperature on Mark-Houwink-Kuhn-Sakurada (MHKS) parameters of chañar brea gum solutions - Torres, Maria Fernanda (2020)
Chañar brea gum (CBG) is a water soluble exudate from the Cercidium praecox tree. The CBG was incorporated into the Argentine Food Code in 2013, due to its ancestral background and its current food uses. CBG could also be used as additive and/or excipient in pharmacological formulations. In this work Mark-Houwink-Kuhn-Sakurada (MHKS) parameters of CBG solutions and temperature effect on hydrodynamic parameters are reported. The analyzed values for this constants indicated a spherical conformation, and it can be concluded that CBG macromolecule has a very good solubility in water.